Novel strategy for manufacturing autologous dendritic cell/allogeneic tumor lysate vaccines for glioblastoma. Issue 1 (26th August 2020) - Parney, Ian F; Gustafson, Michael P; Solseth, Mary; Bulur, Peggy; Peterson, Timothy E; Smadbeck, James B; Johnson, Sarah H; Murphy, Stephen J; Vasmatzis, George; Dietz, Allan B
Abstract: Background: Glioblastoma, the most common primary malignant brain tumor, is nearly universally fatal by 5 years. Dendritic cell vaccines are promising but often limited clinically by antigen choice, dendritic cell potency, and/or manufacturing yield. We optimized vaccine manufacture, generating potent mature autologous dendritic cells pulsed with allogeneic glioblastoma lysates. Methods: Platelet lysate-based supplement was used to establish human glioblastoma cell lines. Phenotype and genotype were assessed. An improved culture technique to generate mature dendritic cells from glioblastoma patients' monocytes was developed. The ability of T cells stimulated with autologous dendritic cells pulsed with allogeneic glioblastoma cell lysate to kill HLA-A2-matched glioblastoma cells was assessed. Results: Glioblastoma cell lines established with platelet lysate supplement grew faster and expressed more stem-like markers than lines grown in neural stem cell media or in the presence of serum. They expressed a variety of glioma-associated antigens and had genomic abnormalities characteristic of glioblastoma stable up to 15 doublings. Unlike standard culture techniques, our optimized technique produced high levels of mature dendritic cells from glioblastoma patients' monocytes. Autologous T cells stimulated with mature dendritic cells pulsed with allogeneic glioblastoma cell line lysate briskly killed HLA-A2-matched glioblastoma cells. Conclusions: Our glioblastoma culture method provides a renewable source for a broad spectrum glioblastoma neoantigens while our dendritic cell culture technique results in more mature dendritic cells in glioblastoma patients than standard techniques. This broadly applicable strategy could be easily integrated into patient care.